The Wesleyan Impulse In Teaching - Thorsen, Donald A. D. (The Asbury journal, 2008)
This professor's pedagogy and theology has long been informed by Wesley, and his essay investigates several themes in Wesley's writings and ministry, including the Wesleyan quadrilateral, experimental religion, catholic spirit, and social holiness. Prom the perspective of teaching theology, the Wesleyan quadrilateral is very useful because it acknowledges the complexity with which Christians formulate their beliefs, values, and practices. Wesley advocated experimentation with regard to how he developed his Christian beliefs, values, and practices leading this professor to use experimental methods in his pedagogy. The catholic spirit prompts him to present theology in a way that includes the breath of Christianity: Protestant and Catholic, Eastern and Western, liberal and conservative high church and low church, and so on. The theme of social holiness leads him to raise students' consciences about social as well as individual dimensions of biblical teaching.